Evolving Customized Service Models and the Role of Dynamic Capabilities in Global National Meteorological Services: A Systematic Literature Review - Anni Arumsari Fitriany; Retno Kusumastuti; Novita Ikasari; Ardhasena Sopaheluwakan (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
National Meteorological Services (NMSs) are increasingly moving beyond their traditional role as publicly funded providers of weather and climate information to deliver customized meteorological services tailored to specific sectors and users. This shift is driven by rising demand for sector-specific climate information, fiscal pressures on public funding, technological advancements, and the growing presence of private weather service providers. This study conducts a systematic literature review to examine how NMSs are evolving their service business models and to analyze the role of dynamic capabilities—specifically sensing, seizing, and transforming—in enabling these organizations to adapt effectively. Following the PRISMA 2020 guidelines, relevant studies published between 2015 and 2025 were identified through Scopus and Google Scholar and analyzed using bibliometric techniques and integrative qualitative synthesis. In addition, a comparative content analysis of official NMS websites across developed, developing, and least developed countries was undertaken to capture real-world service delivery models. The findings reveal that while most NMSs continue to prioritize public service mandates, a growing number are adopting hybrid business models—such as cost-recovery schemes, public–private partnerships, and state-owned enterprise structures—to support customized services. The literature further indicates that dynamic capabilities play a critical role in this transition by enabling NMSs to identify emerging user needs, mobilize organizational and technological resources, and reconfigure service delivery arrangements under regulatory constraints. However, empirical research explicitly linking dynamic capabilities to business model adaptation in NMSs remains limited. This review contributes by synthesizing fragmented insights across public sector, digital government, and service innovation literature, and by highlighting key gaps for future research on strategic transformation in public meteorological institutions.